2000
DOI: 10.1023/a:1005646614308
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The vascular system exhibits altered growth, calcium responses and metabolism during hypertension. To relate such changes, we compared histological, tension and metabolic responses in the aorta from 32-week-old spontaneously hypertensive rats (SHRs), normotensive Wistar-Kyoto (WKY) rats, and SHRs treated with Verapamil (V) and ACE-inhibitor, Trandolapril (T) as well as a combination of the two treatments (C). Vascular hypertrophy was apparent in the SHRs. Contractile responses induced by 50 mmol/1 KCl and 2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…At 20 weeks, there was a four-fold increase in total CK in SHR vs WKY in this study, with blood pressure levels, respectively, 183.3 (7.5) in SHR and 135.0 (5.2) in WKY, which reduced with antihypertensive drugs [ 10 ]. Clark et al also reported significantly higher cytoplasmic CK in 26-week-old male SHR, 0.203, SE 0.014 IU/mg soluble protein vs 0.159, SE 0:01 in WKY [ 11 ]. Finally, Seccia et al found an increase in mitochondrial CK in male SHR by, respectively, 80% at five weeks, to 110% at 24 weeks compared to WKY, with a concurrent increase in SBP (week 5 to 24, respectively, in SHR 123 (SE 10) to 214 (14) vs to 115 (9) to 139 (12) in WKY) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…At 20 weeks, there was a four-fold increase in total CK in SHR vs WKY in this study, with blood pressure levels, respectively, 183.3 (7.5) in SHR and 135.0 (5.2) in WKY, which reduced with antihypertensive drugs [ 10 ]. Clark et al also reported significantly higher cytoplasmic CK in 26-week-old male SHR, 0.203, SE 0.014 IU/mg soluble protein vs 0.159, SE 0:01 in WKY [ 11 ]. Finally, Seccia et al found an increase in mitochondrial CK in male SHR by, respectively, 80% at five weeks, to 110% at 24 weeks compared to WKY, with a concurrent increase in SBP (week 5 to 24, respectively, in SHR 123 (SE 10) to 214 (14) vs to 115 (9) to 139 (12) in WKY) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%